Impact Behavior and Pedestrian Protection of Automotive Laminated Windshield Theories, Experiments and Numerical Simulations - Xu, Jun; Li, Yibing (Springer Nature Singapore : Imprint: Springer, 2019)
This book addresses one of the most important components for pedestrian safety in vehicles - laminated windshields. It includes detailed real-world material characterization results for laminated glass and testing methodologies, constitutive models, and step-by-step numerical simulation modeling and simulation methods. As such, the book provides readers a thorough understanding of the mechanical behaviors of laminated glass and windshields. It also presents fundamental test data, analysis methodologies and essential insights into laminated glass safety design and mechanical behavior prediction. The book addresses the needs of researchers, engineers and postgraduate students in the fields of automotive engineering, mechanical engineering and related areas.